2006
DOI: 10.1002/jso.20503
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemoradiation in rectal cancer: Retrospective comparison between capecitabine and continuous infusion of 5‐fluorouracil

Abstract: Preoperative chemoradiation with oral capecitabine appears to be safe and well tolerated, and at least as good as continuous 5-FU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 21 publications
2
26
1
2
Order By: Relevance
“…In the current trial, even though we performed meticulous pathologic examination described previously, 11 our ypCR rate or other histologic parameters were comparable with other studies that used capecitabine, [16][17][18][23][24][25][26] and our ypCR rate was higher than that of the German trial (17% vs 8%) in spite of more adverse factors (Table 7). 2 The exact reason for these differences is not clear, but we propose the following 2 explanations.…”
Section: Pathologic Responsesupporting
confidence: 84%
See 2 more Smart Citations
“…In the current trial, even though we performed meticulous pathologic examination described previously, 11 our ypCR rate or other histologic parameters were comparable with other studies that used capecitabine, [16][17][18][23][24][25][26] and our ypCR rate was higher than that of the German trial (17% vs 8%) in spite of more adverse factors (Table 7). 2 The exact reason for these differences is not clear, but we propose the following 2 explanations.…”
Section: Pathologic Responsesupporting
confidence: 84%
“…15 However, previous retrospective studies comparing capecitabine and 5-FU indicated that capecitabine was at least as effective as 5-FU in preoperative CRT regimen. [16][17][18][19] The NSABP R-04 trial is expected to provide important information about the efficacy of oral capecitabine versus 5-FU chemotherapy. 20 This trial has completed accrual and the results are pending.…”
Section: Compliance and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…This work is a correlative study, along a separate clinical study that was conducted in that institute for evaluating the effect of neo-adjuvant radiotherapy to the pelvis combined with continuous oral chemotherapy by capecitabine. The patients' demographics, as well as their tumor characteristics, and their clinical results of treatment, are detailed in a separate paper [14]. Our study population included those 32 of their 43 patients from whom we could obtain all the programmed serum samples.…”
Section: Patients Characteristicsmentioning
confidence: 99%
“…2 Current treatment options for CRC include surgery, chemotherapy and radiation therapy, all of which can significantly reduce quality of life. Emerging therapeutic strategies for CRC include the nonsteroidal anti-inflammatory drug, Sulindac, 3 new chemotherapeutics including Capecitabine, 4 and antibodies such as the monoclonal epidermal growth factor receptor (EGFR) antibody, Cetuximab. 5 However, probiotics represent another emerging therapeutic option.…”
mentioning
confidence: 99%